(3GdCZPjIs - (3eMeO Hf YHO Gddg GdHZOGOj, TeS GdOjf GdJSJQjs ((3eOjfI WhS s)
(3ChdgG (B:s
(3GdMeO ddg Ef Gddg JHGQc hJYGdi deG Ndb fhY GdCfSGf GYOd eRGLkG ef LejY GdMjhGfGJ ,hLYd Pdc s
(3BNQgG (B:s
(3hCcKQ ef GSJYeGd eGA GdQhGFM GdWHjI , hGddg GYde s
(3GdfSNI HgG MhGTs
(3fSNI cKjQI GdghGeT hGdebeMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B18 s
Keywords: (3GdWHs